Deep-sea Chondrichthyans associated with the Patagonian toothfish Dissostichus eleginoides fishery off the coast of Peru (Revista de Biología Marina y Oceanografía, 2022)
The deep-sea fishery for Patagonian toothfish (Dissostichus eleginoides) in Peru offers the opportunity to document species that may be new or rare to the region, or possibly new to science. Here, we report specimens caught, photographed and discarded in a vessel operating in the deep-sea fishery for D. eleginoides, during two fishing trips in 2019 and 2020. Five specimens of three chondrichthyan species were caught incidentally at an average depth of 1,489 m. Species identification was done from photographs as specimens were discarded, and they include Centroscyllium cf. nigrum, Bathyraja cf. spinosissima, and Hydrolagus melanophasma. All are new records for Peruvian waters. Continuing the collaboration with commercial fisheries as a source of information for deep-sea species could greatly contribute to improving our understanding of marine biodiversity in Peru and inform conservation decision-making.